2020
DOI: 10.1183/13993003.03569-2020
|View full text |Cite
|
Sign up to set email alerts
|

Cough hypersensitivity and suppression in COPD

Abstract: Cough reflex hypersensitivity (CRH) and impaired cough suppression are features of chronic refractory cough (CRC). Little is known about cough suppression and CRH in cough associated with chronic obstructive pulmonary disease (COPD). This study investigated the ability of participants with COPD to suppress cough during a cough challenge test in comparison to participants with CRC and healthy subjects. This study also investigated whether CRH is associated with chronic cough in COPD.Participants with COPD (n=27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Volitional cough suppression involves a brain network important for general motor response inhibition 107 , 110 , 111 . Patients with refractory chronic cough have attenuated volitional cough suppression 112 , 113 and impaired engagement of this cough inhibition network 101 . Cough and related brain activity are also modulated by acute painful stimuli applied to the skin 86 , 114 , via an extension of the conditioned pain modulation (CPM) phenomenon whereby noxious stimuli applied to one part of the body inhibit the processing of noxious stimuli applied elsewhere.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Volitional cough suppression involves a brain network important for general motor response inhibition 107 , 110 , 111 . Patients with refractory chronic cough have attenuated volitional cough suppression 112 , 113 and impaired engagement of this cough inhibition network 101 . Cough and related brain activity are also modulated by acute painful stimuli applied to the skin 86 , 114 , via an extension of the conditioned pain modulation (CPM) phenomenon whereby noxious stimuli applied to one part of the body inhibit the processing of noxious stimuli applied elsewhere.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Components of these inhibitory systems that regulate cough use the inhibitory neurotransmitter GABA, and GABA receptor agonists modify evoked coughing in animals and in humans 115 , 116 . Patients with COPD do not have altered volitional cough suppression 112 , suggesting that distinct neural endotypes contribute to chronic cough 81 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…COPD patients with chronic cough have significantly lowered capsaicin threshold for cough, meaning that they are more susceptible to cough. However, COPD patients can suppress this cough to a certain degree, which is contrary to patients with refractory chronic cough [9 ▪ ]. As perhaps could be expected, a recent study showed that COPD patients’ cough sensitivity is heightened during exacerbations, as measured by capsaicin test [32 ▪ ].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 93%
“…Also, the central nervous system can inhibit cough signals, but some patients may have a decreased cough inhibition in the central nervous system, further increasing their tendency to cough [7,8]. Mechanistic studies suggest that the causative mechanisms likely differ between different diseases, which may have implications for the choice of treatment [9 ▪ ,10]. These differences may also explain differences in the presentation and burden of cough, but this has not been studied.…”
Section: Cough Mechanismsmentioning
confidence: 99%
“…In another report, chronic cough, or its suppression, was studied in COPD patients and compared to patients with chronic refractory cough (CRC), or to healthy subjects. 162 All subjects with chronic cough, being COPD or CRC patients, had increased HCR when compared to subjects without chronic cough, being COPD patients or healthy individuals. Also, non-coughing COPD patients had comparable cough reflex sensitivity to healthy subjects.…”
Section: Lower Airway Cough Syndromementioning
confidence: 93%